Contribution of Student Level of Understanding in The Concept of Calculated Operations And Their Relationship to Set Operations - Charles Elbinus Barutu (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
The problem in this study is: whether there is a contribution to the level of understanding of the concept of calculated operations against the operation of the association in students of SMP Negeri 1 Balikpapan. This study aims to find out if there is a contribution to the level of understanding of the concept of calculated operations against the operation of the association in students of SMP Negeri 1 Balikpapan. The population of this study is all students of grade VII-A SMP Negeri 1 Balikpapan consisting of 34 students. And as a sample in this study is the whole student. The data analysis technique used is to use non-premetric statistics "sign test". The results of the data analysis showed that tcount < htable or 1 < 1, this means that there is a positive contribution between the mastery of the counting operations against the operation of the student association of SMP Negeri 1 balikpapan. From these results, it is expected that the teachers of mathematics lessons generally and the teachers who teach in grade VII in order to further improve the learning of hitung operations to students so that the learning of the association operations ismore understandable to students